The Role of Church Leadership In Managing Ethnic Diversity In Church Services In Kasih Perumnas, Sorong City - Purnama Sari, Novanty; Fonataba, Rini L.; Sopakua, Samael; Rumahuru, Yance Z.; Rieuwpassa, Habel S.J. (IAKN TORAJA, 2025)
This study aims to examine the role of leadership within the Evangelical Christian Church (GKI) in Sorong City in managing ethnic diversity in a pluralistic society. Cultural and ethnic diversity presents a unique challenge for the church in creating inclusive and harmonious ministry. Using a descriptive qualitative approach, this research reveals that church leadership plays a vital role in fostering awareness of tolerance, creating spaces for dialogue, and designing ministry programs that respect differences. GKI in Sorong applies strategies such as inclusive leadership, cross-ethnic representation in church structures, and the integration of local cultural elements in worship. These findings affirm that the successful management of diversity is a witness to the Gospel and a theological calling to build a respectful and united fellowship in the body of Christ.